2010
DOI: 10.3892/ijo_00000815
|View full text |Cite
|
Sign up to set email alerts
|

L-lactate metabolism can occur in normal and cancer prostate cells via the novel mitochondrial L-lactate dehydrogenase

Abstract: Abstract. Both normal (PTN1A) and cancer (PC3) prostate cells produce high levels of L-lactate because of a low energy supply via the citric cycle and oxidative phosphorylation. Since some mammalian mitochondria possess a mitochondrial L-lactate dehydrogenase (mLDH), we investigated whether prostate cells can take up L-lactate and metabolize it in the mitochondria. We report here that externally added L-lactate can enter both normal and cancer cells and mitochondria, as shown by both the oxygen consumption and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…57,58,59,60 Furthermore, the elevated catalytic efficiency of glycolytic enzyme promoted L-lactate secretion and formed an autocrine lactate loop promoting malignant transformation. 57,61,62 The possible role of llactate metabolism and transport in cancer biochemistry has long been ignored in cancer research 63 and future research is warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…57,58,59,60 Furthermore, the elevated catalytic efficiency of glycolytic enzyme promoted L-lactate secretion and formed an autocrine lactate loop promoting malignant transformation. 57,61,62 The possible role of llactate metabolism and transport in cancer biochemistry has long been ignored in cancer research 63 and future research is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that berberine potently suppressed LDHA-OE pancreatic cancer cell growth. We identified half-maximal inhibitory concentration (IC50) approximately equal to 62 5E). Functionally, exposure of L-lactate to berberine-treated cancer cells attenuated the growth and invasion suppression by berberine (Figure 5F and G), suggesting the restoration of LDHA attenuated the suppressive effect of berberine on PAAD.…”
Section: Berberine As An Ldha Inhibitor Plays Critical Role In Suppressing Ldha/ampk-mtor Mediated Cancer Cell Progressionmentioning
confidence: 99%
“…Surprisingly, such a simple procedure has not been appreciated and accepted in a recent paper [ 7 ] stating that “Unfortunately, some studies which have concluded the existence or absence of mitochondrial LDH, and implied the physiological relevance thereof, base such claims on experiments involving the continuous monitoring of added NADH autofluorescence in isolated mitochondria [ 14 , 18 , 19 , 20 , 21 , 22 , 23 ]”. We believe that the authors misinterpreted the cited papers since NADH was not added to mitochondria.…”
Section: How Mitochondrial Traffic In Energy Metabolism Is Easily and Quickly Investigated?mentioning
confidence: 99%
“…We believe that the authors misinterpreted the cited papers since NADH was not added to mitochondria. Rather, the authors monitored only the fluorescence of the mitochondrial NAD(P)H [ 14 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: How Mitochondrial Traffic In Energy Metabolism Is Easily and Quickly Investigated?mentioning
confidence: 99%
“…This is further evidenced by LDHB localizing to the mitochondria at greater densities than to other locations, and LDHA not localizing to the mitochondria (Chen et al, 2016). Additionally, mitochondrial LDH is highly expressed and more active in cancerous prostate cells than normal ones, contributing to the anaplerosis of TCA cycle intermediates to help fuel cancer progression (De Bari et al, 2010). However, some have demonstrated that lactate must be first converted to pyruvate before it can enter the mitochondrial matrix and have challenged the hypothesis that lactate can be directly oxidized by mitochondria (Jacobs et al, 2013;Passarella et al, 2014).…”
Section: The Role Of Lactate Shuttlesmentioning
confidence: 99%